2007
DOI: 10.1128/jb.01149-06
|View full text |Cite
|
Sign up to set email alerts
|

Response of Staphylococcus aureus to Salicylate Challenge

Abstract: Growth of Staphylococcus aureus with the nonsteroidal anti-inflammatory salicylate reduces susceptibility of the organism to multiple antimicrobials. Transcriptome analysis revealed that growth of S. aureus with salicylate leads to the induction of genes involved with gluconate and formate metabolism and represses genes required for gluconeogenesis and glycolysis. In addition, salicylate induction upregulates two antibiotic target genes and downregulates a multidrug efflux pump gene repressor (mgrA) and sarR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 55 publications
(65 reference statements)
2
63
0
Order By: Relevance
“…Expression of the cap operon and CP expression in S. aureus are known to be under multiple levels of control and affected by several environmental stimuli (49). Previous studies have shown that the global regulators agr, mgrA, arlRS, B , sarA, and saeRS control CP production at the transcriptional level (30,31,34,55,59).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the cap operon and CP expression in S. aureus are known to be under multiple levels of control and affected by several environmental stimuli (49). Previous studies have shown that the global regulators agr, mgrA, arlRS, B , sarA, and saeRS control CP production at the transcriptional level (30,31,34,55,59).…”
Section: Discussionmentioning
confidence: 99%
“…Household disinfectant reduced susceptibility S. aureus mutants demonstrated altered cell wall metabolism (Lamichhane-Khadka et al ., 2008) and a TTORS phenotype (Davis et al ., 2005). S. aureus grown in the presence of salicylate which activates an intrinsic multiple antimicrobial mechanism (Riordan et al ., 2007) also demonstrated TTORS (Gustafson et al ., 2001). …”
Section: Introductionmentioning
confidence: 99%
“…While 5-ASA has not previously been the subject of genomic screens in bacteria, several studies have used microarray analysis to examine the effects of salicylic acid on expression in E. coli, 25 Staphylococcus aureus, 54 and Mycobacterium tuberculosis. 55 In E. coli, for example, salicylate has been shown to regulate transcription of the multiple antibiotic resistance operon marRAB, 24 with marR encoding a negative regulator of the operon and marA encoding a transcriptional activator.…”
Section: Inflamm Bowel Dismentioning
confidence: 99%